Tinjauan Hukum Terhadap Pelanggaran Hak Cipta Dalam Penggunaan Lagu Atau Musik Instrumental SKJ88 Berdasarkan Undang-Undang Hak Cipta - Denis Syahputra; Wilma Silalahi (Dinasti Research, 2025)
Legal protection of Intellectual Property (IPR), especially Copyright, is an important element in the legal system that reflects the aspirations and goals of the state to recognize, respect and protect the intellectual works of its citizens. This protection includes economic rights and moral rights attached to the work, which not only provides benefits to the creator, but also has a positive impact on social and economic development. Considering that IPR is traded globally, strategic steps are needed to protect these rights from misuse or detrimental violations. The copyright infringement case that occurred in the song SKJ88 by O Shop, which was used without permission in product promotion, is a clear example of the importance of legal protection for intellectual works. This case underscores the urgency of more effective law enforcement, including the need for compliance with copyright registration procedures and collaborative publishing arrangements to prevent piracy. This research aims to assess the effectiveness of legal protection for copyright in preventing and dealing with violations of the use of intellectual works for commercial purposes without permission